Características da libras na escrita em português dos surdos - Silva, Letícia Macedo (Universidade Federal de São Carlos, 2025)
Brazilian Sign Language (Libras) is used by deaf people as their primary means of communication, constituting, for many of them, their mother tongue. The objective of this work is to investigate possible influences of Libras parameters on the use of grammatical elements and verbal agreement in written Portuguese by deaf people. To this end, a bibliographic study and an analysis of materials produced by deaf adults were carried out, especially messages from a WhatsApp group, which allowed for observation of writing in spontaneous situations. The selected sentences show that participants resort to the structure of Libras when writing in Portuguese, which explains differences in morphosyntactic organization, such as the absence of connectives, prepositions, and conjunctions. These features, however, should not be seen as "errors," but as natural manifestations of the transition between L1 (Libras) and L2 (Portuguese), reflecting the natural fluidity of sign language linguistics.
Characteristics of libras in the portuguese writing of deaf people
Keywords: Libras; língua portuguesa; gramática; sociolinguística; surdez; LINGUISTICA, LETRAS E ARTES::ARTES; 4. Educação de Qualidade